Organophosphane-Catalyzed Construction of Functionalized 2-Ylideneoxindoles via Direct β-Acylation - Jeng, Wey-Chyng; Chien, Po-Chung; Vagh, Sandip Sambhaji; Edukondalu, Athukuri; Lin, Wenwei (Synthesis, 2021)
We report an efficient method for the direct β-acylation of 2-ylideneoxindoles with acyl chlorides that is catalyzed by organophosphanes in the presence of base. A variety of functionalized 2-ylideneoxindoles were prepared in moderate to good yields under mild, metal-free conditions via a tandem phospha-Michael/O-acylation/intramolecular cyclization/rearrangement sequence. Mechanistic investigations revealed that C–O bond cleavage on a possible betaine intermediate is the key step for the installation of the keto-functionality at the β-position of 2-ylideneoxindoles in a highly stereospecific manner. The synthetic utility of this protocol could also be proven by a scale-up reaction and synthetic transformations of the products.
Keywords: β-acylation; functionalized 2-ylideneoxindoles; indolin-3-ones; phospha-Michael addition; phosphine catalysis